Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport

Loading of CAR‐T cells with magnetic nanoparticles for controlled targeting suppresses inflammatory cytokine release and switches tumor cell death mechanism - Pfister, Felix; Carnell, Lucas; Löffler, Lisa; Boosz, Philipp; Schaft, Niels; Dörrie, Jan; Stein, René; Lenz, Malte; Spiecker, Erdmann; Huber, Christian; Haddadin, Sami; Berking, Carola; et al. (MedComm, 2025)
Therapies against hematological malignancies using chimeric antigen receptors (CAR)-T cells have shown great potential; however, therapeutic success in solid tumors has been constrained due to limited tumor trafficking and infiltration, as well as the scarcity of cancer-specific solid tumor antigens. Therefore, the enrichment of tumor-antigen specific CAR-T cells in the desired region is critical for improving therapy efficacy and reducing systemic on-target/off-tumor side effects. Here, we functionalized human CAR-T cells with superparamagnetic iron oxide nanoparticles (SPIONs), making them magnetically controllable for site-directed targeting. SPION-loaded CAR-T cells maintained their specific cytolytic capacity against melanoma cells expressing the CAR-specific antigen chondroitin sulfate proteoglycan (CSPG4). Importantly, SPIONs suppressed cytokine release in the loaded CAR-T cells, shifting the cell death phenotype in the tumor cells from pyroptosis to apoptosis. Furthermore, SPION-loaded CAR-T cells could be enriched in a dynamic flow model through an external magnetic field and be detected in MRI. These results demonstrate that lytic cytotoxicity is retained after SPION-functionalization and provides a basis for future site-specific immunotherapies against solid tumors with reduced systemic adverse side effect